2005
DOI: 10.1038/sj.embor.7400403
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of protein energy landscape roughness

Abstract: The energy landscape of proteins is thought to have an intricate, corrugated structure. Such roughness should have important consequences on the folding and binding kinetics of proteins, as well as on their equilibrium fluctuations. So far, no direct measurement of protein energy landscape roughness has been made. Here, we combined a recent theory with single-molecule dynamic force spectroscopy experiments to extract the overall energy scale of roughness e for a complex consisting of the small GTPase Ran and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
111
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 38 publications
10
111
1
Order By: Relevance
“…[66] It was shown that energy surfaces of single transmembrane a-helices, as well as pairs, contain considerable local energy corrugations with a roughness scale (e) of % 5 k B T (Figure 6 b). [66] Since a rough energy surface is a prerequisite for functionally related conformational changes and local flexibilities, [5,11,95] the finding that the energy surfaces of transmembrane a-helices are rugged is in line with the vital roles of ahelices as structural and functional building blocks. The determined energy surface ruggedness of transmembrane a-helices is of the same magnitude as that of short peptides ( % 2 k B T), small globular proteins (< 5 k B T), and the force-induced dissociation of two interacting proteins ( % 5 k B T) or DNA strands ( % 10 k B T).…”
Section: Transmembrane A-helices Have Rough Energy Surfacesmentioning
confidence: 86%
See 1 more Smart Citation
“…[66] It was shown that energy surfaces of single transmembrane a-helices, as well as pairs, contain considerable local energy corrugations with a roughness scale (e) of % 5 k B T (Figure 6 b). [66] Since a rough energy surface is a prerequisite for functionally related conformational changes and local flexibilities, [5,11,95] the finding that the energy surfaces of transmembrane a-helices are rugged is in line with the vital roles of ahelices as structural and functional building blocks. The determined energy surface ruggedness of transmembrane a-helices is of the same magnitude as that of short peptides ( % 2 k B T), small globular proteins (< 5 k B T), and the force-induced dissociation of two interacting proteins ( % 5 k B T) or DNA strands ( % 10 k B T).…”
Section: Transmembrane A-helices Have Rough Energy Surfacesmentioning
confidence: 86%
“…Based on Zwanzig's work Hyeon and Thirumalai recently established the basis for experimentally probing the roughness of two-state energy landscapes (Figure 6 a) using DFS at different temperatures. [94] A modified form of the model [95] was combined with temperature-dependent DFS experiments to determine the energy landscape roughness of the transmembrane a-helices of bacteriorhodopsin. [66] It was shown that energy surfaces of single transmembrane a-helices, as well as pairs, contain considerable local energy corrugations with a roughness scale (e) of % 5 k B T (Figure 6 b).…”
Section: Transmembrane A-helices Have Rough Energy Surfacesmentioning
confidence: 99%
“…The requirement of gp120 mutations for maC46 resistance, which was not observed for resistance to soluble CFI, could be explained by the different modes of binding to the target site for soluble and membrane-bound C peptides. Peptides are not rigid structures but are better represented as a manifold of low-energy conformations and conformational substrates (energy landscape) (4,20,26). The binding of a flexible soluble peptide to its target is governed purely by random molecular diffusion, and it can therefore be assumed that upon its first encounter with the target region, only a small segment of each peptide will be aligned correctly.…”
Section: Vol 83 2009mentioning
confidence: 99%
“…Recently, single-molecule techniques have been used to probe features of the energy landscape of proteins and RNA that are not easily accessible in ensemble experiments (7-18). It is possible to construct the shape of the energy landscape, including the energy scales of ruggedness (19,20), by using dynamical trajectories that are generated by applying a constant force ( f ) to the ends of proteins and RNA (14,15,21,22). If the observation time is long enough for the molecule to sample the accessible conformational space, then the time average of an observable X recorded for the ␣th molecule [͗X͘ ϭ t3ϱ…”
mentioning
confidence: 99%